Virtually engaged: the effect of a virtual work environment on task engagement, its antecedents, and consequences - Hurd, Brian M., author; Byrne, Zinta S., advisor; Kraiger, Kurt K., committee member; Steger, Michael F., committee member; Cross, Jennifer E., committee member (Colorado State University. Libraries, 2011)
As organizations continue to adopt virtual work environments in an effort to reduce costs and offer employees greater flexibility, the effect of this work setting on employee engagement is not fully understood. This laboratory study investigates the effect of a virtual work environment on participant perceptions (N = 242) of engagement, its antecedents, and consequences in an effort to extend the Job Demands-Resources model of employee engagement (JD-R; Bakker & Demerouti, 2007). Specifically, it was proposed that the JD-R be expanded to include contextual variables (e.g., work environment) and that these variables potentially influence individuals' appraisals of whether a work variable is a resource or a demand. To test this modified model, participants were assigned to work on a marketing task in either a virtual (N = 126) or co-located environment (N = 116). Results revealed that task engagement, quality of coworker relations, social presence, task performance, and task satisfaction were all higher and team uncertainty was lower for those working in a co-located environment compared to those working virtually. Team uncertainty and social presence partially mediated the relationship between work environment and quality of coworker relations. Team uncertainty was higher and social presence was lower for those working virtually as compared to those who were co-located, which in turn resulted in perceptions of reduced quality of coworker relations. Furthermore, task engagement fully mediated the relationship between quality of coworker relations and both performance and effort, and task engagement partially mediated the relationship between quality of coworker relations and task satisfaction. Quality of coworker relations was positively related to task engagement, which was related to increased task performance, effort, and task satisfaction. When combined, the results provide support for the proposed expansion of the JD-R to include contextual variables. Because resources and demands are fundamental to the JD-R and determine when employees become engaged versus disengaged, this extension to the model makes a significant contribution to the employee engagement and virtual work literatures. These results also offer practical applications for those organizations that operate virtual work environments.
Keywords: electronic communication; virtual; performance; engagement